Kajian Praktis Tentang Pola Asuh Orang Tua dalam Meningkatkan Minat Belajar Alkitab Anak Berdasarkan Amsal 22:6 - Dadan Wahyu; Rudolf Sagala; Stimson Hutagalung; Rolyana Fernia (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2021)
The objectives of this study are, first, to provide an explanation of the importance of parenting. Second, Provide guidance to parents in building spiritual children based on the book of Proverbs 22:6. The method that the researcher uses is a qualitative method with a grounded theory approach. Data collection techniques used: the Bible, books, official sources from the internet, and other articles related to the writing of this scientific article. The results of this study are, first, good parenting will encourage children to have an interest in reading the Bible regularly until their old age. Second, so that parents can understand properly and correctly the meaning of the advice written in the book of Proverbs 22:6 in raising their children. That is why parents and the Church from the beginning have played a role in the protection and maintenance of their lives, so that they know the way of truth through God's word every day, so that they become strong individuals in the future, strong in their faith, and fearing God to make life a blessing or meaning to others.